A novel bilayer hydrogel/ fibrous wound dressing with Falcaria vulgaris extract and green synthesized ZnO nanoparticles for enhanced wound healing - Tahereh Moshfeghi; Najmeh Najmoddin; Elham Arkan; Leila Hosseinzadeh (Journal of Science: Advanced Materials and Devices)
Since wound healing is a multifaceted process, most conventional scaffolds do not resemble the complexity of the natural extracellular matrix. Thus, they cannot provide a suitable niche for endogenous tissue reconstruction. To overcome this issue and to accelerate the healing process, we developed a biomimetic double-layer dressing comprising sodium alginate/gelatin hydrogel loaded with Falcaria Vulgaris extract and green synthesized zinc oxide nanoparticles (ZnO NPs) as the dermal layer and electrospun polyacrylonitrile (PAN) nanofibers as the epidermis matrix. FESEM images confirmed the existence of bead-free, smooth, and continuous PAN fibers with proper binding on the surface of the hydrogel. The multifunctional double layer dressing revealed admirable mechanical characteristics including tensile strength (5 ± 0.05 MPa), elastic modulus (0.4 ± 0.1 MPa) and elongation at break (50 ± 5 %) along with proper swelling capacity and degradation rate. Such dressing exhibited an inhibition zone against both gram-negative (20 ± 2 mm) and gram-positive (21 ± 2 mm) bacterial strains via controlled release of ZnO NPs without any toxicity in the vicinity of L929 cells. The high potency of such intriguing bilayer dressing for wound repair was further confirmed via the promotion of wound contraction, collagen synthesis, re-epithelialization, and new tissue formation during in vivo assay.